The characteristics of shoulder muscles in archery athletes - Kim, R. N.; Lee, J.-H.; Hong, S. H.; Jeon, J. H.; Jeong, W. K. (Clinics in Shoulder and Elbow, 2018)
Background: This study evaluated the shoulder girdle muscle characteristics of elite archery athletes and provides suggestions for archery training programs. Methods: This study enrolled 15 cases of high level archery athletes (7 males, 8 females) and 30 cases of (15 males, 15 females) sex, age-matched, healthy, non-athletic individuals. We measured peak torques of flexion (FL), extension (EX), abduction (ABD), adduction (ADD), external rotation (ER) and internal rotation (IR) of both shoulders at an angular velocity of 30°/sec, 60°/sec, and 180°/sec. The peak torques and peak torque ratios of FL/EX, ABD/ADD, and ER/IR of the two groups were compared. Results: The archer group had a greater peak torque of IR and ADD, but only in the left shoulder (p<0.05). In the same group, both shoulders had greater peak torque of EX and lower peak torque of FL. The peak torque ratios of FL/EX of both shoulders were significantly lower in the archer group at all three angular velocities (p<0.05). The peak torque ratios of ABD/ADD were significantly greater in only the left shoulder of the archer group (p<0.05). Conclusions: The prominent characteristics of the shoulder girdle muscles of an elite archer are stronger adductor muscles of the bow shoulder and stronger extensors of both shoulders, as compared to healthy, non-athletic individuals. These muscle groups of the shoulder probably contribute a major role in maintaining the accuracy and stability during archery shooting. Hence, a training program that selectively enhances the adductor and extensor muscles could prove helpful in enhancing the archery skills of the athlete.